Protection of Steel Rebar in Salt-Contaminated Cement Mortar Using Epoxy Nanocomposite Coatings - The Huu Nguyen; Tuan Anh Nguyen (International Journal of Electrochemistry)
Epoxy reinforced with two kinds of nanoparticles dealing with nano-SiO2 and nano-Fe2O3 was coated on steel rebar embedded in a chloride contaminated cement mortar. NaCl was added to the fresh Portland cement paste (at 0.3% and 0.5% by weight of cement) to simulate the chloride contamination at the critical level. The effect of incorporating nanoparticles on the corrosion resistance of epoxy-coated steel rebar was investigated by linear potentiodynamic polarization and electrochemical impedance spectroscopy. For the 0.3 wt.% chloride mortars, the electrochemical monitoring of the coated steel rebars during immersion for 56 days in 0.1 M NaOH solutions suggested the beneficial role of nano-Fe2O3 particles in significantly improving the corrosion resistance of the epoxy-coated rebar. After 56 days of immersion, the nano-Fe2O3 reduced the corrosion current of epoxy-coated rebar by a factor of 7.9. When the chloride concentration in the cement mortar was 0.5 wt.%, the incorporation of nanoparticles into the epoxy matrix did not enhance the corrosion resistance of epoxy coating for the rebar. At this critical level, chloride ions initiated rebar corrosion through nanoparticles at the epoxy/rebar interface.